2016
DOI: 10.5194/hess-20-3393-2016
|View full text |Cite
|
Sign up to set email alerts
|

Recent changes and drivers of the atmospheric evaporative demand in the Canary Islands

Abstract: Abstract. We analysed recent evolution and meteorological drivers of the atmospheric evaporative demand (AED) in the Canary Islands for the period 1961-2013. We employed long and high-quality time series of meteorological variables to analyse current AED changes in this region and found that AED has increased during the investigated period. Overall, the annual ET o , which was estimated by means of the FAO-56 Penman-Monteith equation, increased significantly by 18.2 mm decade −1 on average, with a stronger tre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…Also, based on a newly developed homogeneous gridded database that employed the most available stations from the telecommunication system of the WMO, Willett et al (2014) found significant negative changes in RH, with strong spatial variability, at the global scale. This global pattern was also confirmed at the regional scale, but with different signs of change, including both negative (e.g., Vincent et al, 2007;Vicente-Serrano et al, 2014bZongxing et al, 2014) and positive trends (e.g., Shenbin et al, 2006;Jhajharia et al, 2009;Hosseinzadeh Talaee et al, 2012).…”
mentioning
confidence: 75%
“…Also, based on a newly developed homogeneous gridded database that employed the most available stations from the telecommunication system of the WMO, Willett et al (2014) found significant negative changes in RH, with strong spatial variability, at the global scale. This global pattern was also confirmed at the regional scale, but with different signs of change, including both negative (e.g., Vincent et al, 2007;Vicente-Serrano et al, 2014bZongxing et al, 2014) and positive trends (e.g., Shenbin et al, 2006;Jhajharia et al, 2009;Hosseinzadeh Talaee et al, 2012).…”
mentioning
confidence: 75%
“…Second, the “observed” radiative and aerodynamic components were calculated from meteorological data based on a modified Penman equation (PenPan model) due to no direct measurements available, which may inherit some uncertainty as well. For example, the radiative component of pan evaporation was estimated from the sunshine duration, which is strongly influenced by the cloud coverage and aerosol [ Stanhill and Cohen , ; Zhou and Du , ; Wild , ]; based on that, the sunshine duration has showed adequate capacity to construct long‐term radiation and was widely applied in many countries and regions [ Wang et al ., ; Azorin‐Molina et al ., ; Vicente‐Serrano et al ., ]. Moreover, several other improvement need also to be made in the PenPan model, especially in the calculation of the pan albedo and more accurate treatment of pan's incoming and outgoing long‐wave radiations [ Rotstayn et al ., ; Roderick et al ., ; Li et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…Focusing on physical models calculated from meteorological data, there have been numerous recent regional studies analyzing AED trends using Penman's equation (Penman, ). These studies show both positive (Gocic & Trajkovic, ; Piticar et al, ; Vicente‐Serrano, Azorin‐Molina, Sanchez‐Lorenzo, Revuelto, López‐Moreno, et al, ; Vicente‐Serrano, Azorin‐Molina, Sanchez‐Lorenzo, Revuelto, Morán‐Tejeda, et al, ; Vicente‐Serrano, Lopez‐Moreno, et al, ; Vicente‐Serrano et al, ) and negative (Jhajharia et al, ; H. Wang et al, ; Q. Wang et al, ; Z. Wang et al, ) trends in different regions. Over the globe K. Wang et al () used more than 4,200 stations were used to estimate AED trends between 1982 and 2008.…”
Section: Aed‐related Drought Trendsmentioning
confidence: 94%